Factors associated with obtaining prescribed safer supply among people accessing harm reduction services: findings from a cross-sectional survey - Heather Palis; Beth Haywood; Jenny McDougall; Chloé G. Xavier; Roshni Desai; Samuel Tobias; Heather Burgess; Max Ferguson; Lisa Liu; Brooke Kinniburgh; Amanda K. Slaunwhite; Alexis Crabtree; et al. (BMC, 2024)
Abstract Background With growing rates of unregulated drug toxicity death and concerns regarding COVID-19 transmission among people who use drugs, in March 2020, prescribed safer supply guidance was released in British Columbia. This study describes demographic and substance use characteristics associated with obtaining prescribed safer supply and examines the association between last 6-month harm reduction service access and obtaining prescribed safer supply. Methods Data come from the 2021 Harm Reduction Client Survey administered at 17 harm reduction sites across British Columbia. The sample included all who self-reported use of opioids, stimulants, or benzodiazepines in the prior 3 days (N = 491), given active use of these drugs was a requirement for eligibility for prescribed safer supply. The dependent variable was obtaining a prescribed safer supply prescription (Yes vs. No). The primary independent variables were access to drug checking services and access to overdose prevention services in the last 6 months (Yes vs. No). Descriptive statistics (Chi-square tests) were used to compare the characteristics of people who did and did not obtain a prescribed safer supply prescription. Multivariable logistic regression models were run to examine the association of drug checking services and overdose prevention services access with obtaining prescribed safer supply. Results A small proportion (n = 81(16.5%)) of the sample obtained prescribed safer supply. After adjusting for gender, age, and urbanicity, people who reported drug checking services access in the last 6 months had 1.67 (95% CI 1.00-2.79) times the odds of obtaining prescribed safer supply compared to people who had not contacted these services, and people who reported last 6 months of overdose prevention services access had more than twice the odds (OR 2.08 (95% CI 1.20-3.60)) of prescribed safer supply access, compared to people who did not access these services. Conclusions Overall, the proportion of respondents who received prescribed safer supply was low, suggesting that this intervention is not reaching all those in need. Harm reduction services may serve as a point of contact for referral to prescribed safer supply. Additional outreach strategies and service models are needed to improve the accessibility of harm reduction services and of prescribed safer supply in British Columbia.